Relationship between the morphology of the greater tuberosity and radiological and clinical outcomes after arthroscopic rotator cuff repair - Kawashima, Kenji; Sugaya, Hiroyuki; Takahashi, Norimasa; Matsuki, Keisuke; Takeuchi, Yasutaka; Terabayashi, Nobuo; Akiyama, Haruhiko (JSES International, 2021)
Degenerative greater tuberosity (GT) changes are often associated with rotator cuff tears. However, little is known about the impact of GT morphology on surgical outcomes. The aim of this study was to examine the relationship between clinical and radiological outcomes, after rotator cuff repair, and GT morphology. We retrospectively investigated shoulders that underwent arthroscopic repair of nontraumatic full-thickness supra-/infraspinatus tears. The exclusion criteria were a lack of either radiographs or magnetic resonance images, revision surgery, partial repair, complications such as infection or dislocation, and follow-up < 2 years. GT morphology on radiographs was classified into 5 groups: normal, sclerosis, bone spur, roughness, and femoralization. The acromiohumeral interval (AHI) was measured on anteroposterior radiographs. Fatty degeneration of the cuff muscles was evaluated using the global fatty degeneration index (GFDI). Postoperative cuff integrity was classified using Sugaya's classification at 2 years after surgery. Clinical outcomes were assessed preoperatively and at postoperative 2 years with the Japanese Orthopaedic Association score and the University of California, Los Angeles shoulder rating scale. The study included 220 shoulders in 212 patients (104 men and 108 women), with a mean age of 66 years (range 43-85). The mean follow-up period was 28 months (range, 24-60 months). Seven shoulders (3.2%) were classified as normal, 65 (29.5%) as sclerosis, 55 (25.0%) as bone spur, 78 (34.5%) as roughness, and 15 (6.8%) as femoralization. The preoperative AHI, in the roughness and femoralization groups, was significantly smaller than that in the sclerosis (P < .01) and bone spur groups (P < .001). The roughness and femoralization groups had a greater number of large tears (P = .006). In the roughness and femoralization groups, mean GFDI was significantly higher than that in the sclerosis group (P < .001 for both). Repaired cuff integrity was not different between all groups, respectively. Both Japanese Orthopaedic Association and University of California, Los Angeles scores improved postoperatively from 73.3 to 95.6 points and 18.2 to 34.0 points (P < .001 for both), respectively, and there were no significant differences between all groups, respectively. Roughness or femoralization of the GT was related to larger tears, with smaller AHI and higher GFDI. Repaired cuff integrity and clinical outcomes in shoulders with roughness or femoralization of the GT were not inferior to shoulders with the other types of GT morphologies in this study. Arthroscopic repair can be indicated for shoulders with advanced changes of the GT, if fatty degeneration of the cuff muscles is not severe.